2016
DOI: 10.6000/1927-3037.2016.05.01.3
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Phospholipases C from some Bacillus thuringiensis Isolates Recovered from Egyptian Soil

Abstract: Two hundred and thirty one isolates, with the characteristic morphology of Genus Bacillus, were recovered from 100 soil samples collected from 7 different Egyptian governorates, and were screened for phospholipase C (PLC) production by egg-yolk plate method. Sixty isolates have shown very high PLC production and were further assessed using chromogenic assay method. The highest five producers, identified by 16S rRNA gene sequencing as Bacillus thuringiensis, were selected and their PLCs were purified to homogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…The extracellular lipase of Bacillus subtilis (Ma et al 2018) was reported. Additionally, Aboulwafa et al (2016) reported that B. thuringiensis is a strong producer (Pz = 0.49 in the current study). Genes encoding degradative lipases have been studied (Dubois et al 2012;Slamti et al 2014).…”
Section: Determination Of Lipolytic Activitysupporting
confidence: 63%
“…The extracellular lipase of Bacillus subtilis (Ma et al 2018) was reported. Additionally, Aboulwafa et al (2016) reported that B. thuringiensis is a strong producer (Pz = 0.49 in the current study). Genes encoding degradative lipases have been studied (Dubois et al 2012;Slamti et al 2014).…”
Section: Determination Of Lipolytic Activitysupporting
confidence: 63%
“…For purification of PC-PLC from a strain of B. thuringiensis isolated from Egyptian soil, Aboulwafa et al [ 68 ] reported a salting-out step with ammonium sulfate and molecular-sieve chromatography on Sephadex G-75. Eddelech and coworkers [ 69 ] have purified PC-PLC from a Tunisian strain of B. thuringiensis using ammonium sulfate precipitation, followed by Sephadex G-75 and Q-Sepharose column chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained pellets were dispersed in 0.05 M Tris-HCl buffer (pH 8.6). The prepared suspension was dialyzed in a dialysis tube with molecular weight cut-off 13,000Da against 250 ml of the same buffer with stirring at 4 °C overnight (Elleboudy et al 2016 ). The dialyzed enzyme was subjected for further purification by loading into Sephadex G-100 size exclusion column (2.5* 30 cm).…”
Section: Methodsmentioning
confidence: 99%
“…Also, they were tested for L-asparaginase activity. The active fractions of L-asparaginase were pooled and used for further analysis (Elleboudy et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%